2000
DOI: 10.3131/jvsj.43.1120
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth of Low-Temperature Processed Poly-Si by Excimer Laser Annealing. Dependences of Poly-Si Grain on Energy Density and Shot Number.

Abstract: This paper examines the characteristics of the poly-Si grains formed by ELA with the energy density from 75 mJ/ cm2 to 400 mJ/cm2, and discusses the change of the crystal growth mechanism of the recrystallized poly-Si dependent on the energy density. For the energy density from 250 mJ/cm2 to 350 mJ/ cm2 , the disk-shaped grains are observed. The dependences of the area ratio of disk-shaped grain both on the energy density and on the shot number are examined. From these results, the role of the disk-shaped grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The reason for this may be that a-or poly-Siˆlm is melted by ELA at 550 mJ/cm 2 and crystallization from the supercooled liquid occurs. We observed the crystal growth from supercooled liquid at 400 mJ/cm 2 for a 100-nm-thickˆlm; 14) therefore, the same phenomenon is considered to be observed at 550 mJ/cm 2 in the present experiment. Here, the grain boundary may be melted by laser irradiation above 150 mJ/cm 2 , where a-Siˆlm becomes poly-Siˆlm.…”
Section: Methodssupporting
confidence: 52%
“…The reason for this may be that a-or poly-Siˆlm is melted by ELA at 550 mJ/cm 2 and crystallization from the supercooled liquid occurs. We observed the crystal growth from supercooled liquid at 400 mJ/cm 2 for a 100-nm-thickˆlm; 14) therefore, the same phenomenon is considered to be observed at 550 mJ/cm 2 in the present experiment. Here, the grain boundary may be melted by laser irradiation above 150 mJ/cm 2 , where a-Siˆlm becomes poly-Siˆlm.…”
Section: Methodssupporting
confidence: 52%
“…[1][2][3][4][5][6] We have studied the crystal growth mechanism of the poly-Si film prepared by multipulse ELA at a low energy density to achieve poly-Si grain enlargement. [7][8][9][10][11][12][13][14] The results of electron spin resonance (ESR) measurement for an ELA poly-Si film indicated that the density of defects at grain boundary, such as dangling bonds, is much larger than that of in-grain defects. 7) The hydrogen in an amorphous silicon (a-Si) film strongly affects the spin density even after the recrystallization of the poly-Si film by ELA.…”
Section: Introductionmentioning
confidence: 99%
“…The increase rate of temperature, the maximum temperature and the vacuum pressure were 60 C/ min, 600 C and 7 Â 10 À7 Pa, respectively. 19,23,29) and textured grains are observed on the quartz substrate. The secondary grain growth is observed on the SiO 2 /glass substrate.…”
Section: Ela and Analysis Of The Filmmentioning
confidence: 98%
“…16,17) On the basis of these results, a new crystal growth model was presented. [18][19][20][21] The purpose of this paper is to review the characteristics of the poly-Si film recrystallized by the ELA method. [22][23][24][25][26] First, the influence of the secondary grain growth on the stress relaxation of poly-Si film is explained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation